Validity of Environmental Education E-Module Based on Education for Sustainable Development Using Flipcreator Platform to Develop Environmental Awareness in Geography Education Students at Khairun University - Rasyid, Rusman; Agustan, Andi Tenri Pada; Aryuni, Vrita Tri; Maru, Rosmini; Mufiana, Ita; Soamole, Handri (PT Mattawang Mediatama Solution, 2024)
This research aims to analyze the validity of the environmental education e-module based on Education for Sustainable Development (ESD) to foster environmental awareness of Educational Geography students at Khairun University. The research method used was Research and Development (R&D) with the ADDIE development model. This research was conducted only at three stages of the five stages of the ADDIE model, namely analyze, design and development, while the implementation and evaluation stages were not carried out because this research and development was only limited to the development stage which was focused on the validity test process. The data analysis techniques used in this research were qualitative descriptive and quantitative descriptive analysis techniques. Qualitative descriptive analysis was used to process data reviews from material/content experts and media and design experts which were used to revise the development product. While quantitative descriptive analysis was used to process the data obtained through validation sheets. The results of this research showed that the validity value of the material/content expert validator and media and design experts on the environmental education e-module based on Education for Sustainable Development (ESD) that was developed had very valid, therefore it is suitable to use in the learning process. This can be seen from the validity of the e-module material/content feasibility reaching a score of 91.25% and the validity of the media and design feasibility reaching a score of 90.38%. In addition, the e-module is also packaged using the Flipcreator Platform which displays text, images, animations, and videos so that it is interesting to learn and easy for students to use anytime and anywhere independently in order to foster an attitude of caring for the environment.